2015
DOI: 10.1088/0004-637x/803/2/49
|View full text |Cite
|
Sign up to set email alerts
|

Kepler-432: A Red Giant Interacting With One of Its Two Long-Period Giant Planets

Abstract: We report the discovery of Kepler-432b, a giant planet ( = 3.9 days), and adaptive optics imaging revealed a nearby (  0. 87), faint companion (Kepler-432B) that is a physically bound M dwarf. The host star exhibits high signal-to-noise ratio asteroseismic oscillations, which enable precise measurements of the stellar mass, radius, and age. Analysis of the rotational splitting of the oscillation modes additionally reveals the stellar spin axis to be nearly edge-on, which suggests that the stellar spin is like… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 136 publications
0
28
0
Order By: Relevance
“…Two additional planethosting evolved stars have had their line-of-sight stellar inclination measured via asteroseismology. Quinn et al (2015) found the super-Jupiter Kepler-432b to be spin-orbit aligned in a eccentric, with a 53 day period orbit around a red- Figure 6. Model evolutionary tracks of effective temperature-luminosity (left) and effective temperature-stellar density (right) from the Geneva isochrones (Ekström et al 2012) are plotted for solar metallicity stars of various masses and rotation rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional planethosting evolved stars have had their line-of-sight stellar inclination measured via asteroseismology. Quinn et al (2015) found the super-Jupiter Kepler-432b to be spin-orbit aligned in a eccentric, with a 53 day period orbit around a red- Figure 6. Model evolutionary tracks of effective temperature-luminosity (left) and effective temperature-stellar density (right) from the Geneva isochrones (Ekström et al 2012) are plotted for solar metallicity stars of various masses and rotation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transit surveys have successfully discovered planets around high mass stars. These include planets around subgiants and giants whose shallow transits were identified by Kepler (e.g., Kepler-56b,c, Huber et al 2013;Kepler-91b, Lillo-Box et al 2014;Kepler-432b, Ciceri et al 2015, Quinn et al 2015KOI-206b and KOI680b, Almenara et al 2015;and K2-39b, Van Eylen et al 2016) and hot-Jupiters around main-sequence A-stars confirmed via Doppler tomography (WASP-33b, Collier Cameron et al 2010b;Kepler-13b, Shporer et al 2011, Szabó et al 2011, Johnson et al 2014; HAT-P-57b, Hartman et al 2015;and KELT-17b, Zhou et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The great diversity of discovered planetary systems is bringing a number of fundamental clues about the processes of planet formation and evolution. Moreover, Kepler has also revealed exoplanets around a diversity of hosts from M-dwarfs (Dressing & Charbonneau 2015) to giant stars (Quinn et al 2015) and binaries (Doyle et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We obtained the following orbital parameter for HIP 67851 c: P = 2131.8 ± 88.3 d, m c sin i = 6.0 ± 0.8 M J , and e = 0.17 ± 0.06. Apart from HIP 67851, there are eight giant stars (log g < ∼ 3.6) that are known to host multiplanet systems 3 : namely, 24 Sextantis and HD 200964 (Johnson et al 2011), HD 4732 (Sato et al 2013 (Huber et al 2013), Kepler 432 (Ciceri et al 2015;Ortiz et al 2015;Quinn et al 2015), Kepler 391 (Rowe et al 2014), η Ceti (Trifonov et al 2014), and TYC 1422-614-1 (Niedzielski et al 2015. Interestingly, η Ceti is the only one that is located in the clump region, although according to Trifonov et al (2014) it is most likely a RGB star instead of a HB star.…”
Section: Summary and Discussionmentioning
confidence: 99%